SITE INDEX OF SIAMESE ROSEWOOD (Dalbergia cochinchinensis Pierre) IN PLANTATIONS OF THAILAND - Taengmoo Phunchaisri; Chongrak Wachrinrat; Ponthep Meunpong; Suwan Tangmitcharoen; Nawaphong Kuasakun (SEAMEO BIOTROP, 2020)
Currently, decreased productivity of Siamese rosewood (Dalbergia cochinchinensis Pierre) is a problem due to illegal logging and the guidelines to manage this prevention may be insufficient. Forest plantations should be promoted to achieve sustainable wood production for this species. Site index (SI) is a measure that can be used to predict forest productivity to identify appropriate sites for planting Siamese rosewood. The objective of the current study was to predict the SI for Siamese rosewood in Thailand. A sample of 78 temporary plots at 26 sites in 16 provinces of Thailand was selected to construct a site index curve with a base age of 30 years. The results showed that the mean age of Siamese rosewood was 28 years (between 13 and 55 years), the mean diameter at breast height (DBH) was 20.03 cm (between 7.99 and 33.80 cm), and the mean dominant height was 20.79 m (between 7.32 and 24.82 m). The SI equation was: SI = 0.406 at p < 0.0001 (chosen as 30 years in the present study). The equation indicated that 14, 18, 22, 26, and 30 m trees belonged to site classes I, II, III, IV, and V, respectively. Although in natural forests Siamese rosewood is distributed in dry evergreen and mixed deciduous forests, in the present study, several sites in areas under both in situ and ex situ conservation were in the good and very good site categories. Thus, both areas can be used to plant Siamese rosewood and increase its productivity.